Authority and Dissent in Jewish Life - Greenspoon, Leonard J. (Leonard Jay); Project Muse. (West Lafayette : Purdue University Press, 2020)
"Throughout the long history of Judaism, many individuals and groups have sought to wield authority on the basis of unique religious, social, familial, military, or political claims. Moving historically from the biblical period to the modern-day State of Israel, Authority and Dissent in Jewish Life discusses a range of those claims to authority from within the Jewish community itself. There is no single paradigm that characterizes these instances. Yet again and again the same causes of disagreement arise: interpretation and application of authoritative texts, appropriate ways to remember and memorialize figures from the past, the extent to which traditional leadership roles should (or should not) change in keeping with new cultural or political contexts, the degree to which long-held beliefs and long-practiced rituals are (or are not) susceptible to modification or abandonment, and the tension members of a Jewish community may feel when their leaders make pronouncements at odds with the political policies of the secular state in which they live. Written accessibly, the essays in this collection examine these phenomena from a wide variety of approaches, genres, and media. They pay close attention to the historical and religious settings of the controversies they analyze, yet also allow for ample reflection on the larger issues of authority and dissent that each occurrence raises"--
Acknowledgments -- Editor's Introduction -- Contributors -- Figurative Language of Authority and Rebellion in the Story of the Death of Rabbi Judah ben Bava / Chen Marx -- Midrash, Oral Law, and the Question of Rabbinic Authority / Azzan Yadin-Israel -- Dissenting Literature and Social Formation in the Antique Mediterranean / Zachary B. Smith -- When the Memory of David Is Not Enough to Authenticate the Temple in Jerusalem / Joel Gereboff -- From Acosta and Spinoza to Arendt to Laurence and Aylon: Verbiage and Visual Art as Instruments of Dissent in Modern Jewish Thought / Ori Z. Soltes -- Jewish Law and the Law of the State: A Study in Authority and Dissent / Gil Graff -- The Terrible Animal Known as the Masses: The Status and Authority of the Community Rabbi in Nineteenth Century Eastern Europe / Motti Zalkin -- Thumbing Mendelssohn's Nose at the Nazis: Hans Pfitzner's Symphony in C, Op. 46 (1940) / Theodore Albrecht -- Not So Silent: Jewish Religious and Cultural Life in Kiev, 1945-1970s / Victoria Khiterer -- When Authority Was a Form of Dissent: Postwar Guides to Reform Practice / Joan S. Friedman -- Dispute for the Sake of Heaven: Dissent and Multiplicity in Rav Shagar's Thought / Eitan Abramovitch -- Limiting the Authority of the Country: Disobedience in the IDF / Shlomo Abramovich -- Leaving the Fold: Dissent from Communal Authority in the Orthodox World? / Mark Trencher -- Brit without Milah: Adapting and Remixing the Dominant Ritual System / Lindsey Jackson.
"Proceedings of the Thirty-First Annual Symposium of the Klutznick Chair in Jewish Civilization, the Harris Center for Judaic Studies, and the Schwalb Center for Israel and Jewish Studies, October 28-29, 2018"--1st preliminary page.
Includes bibliographical references.
Description based on print version record.
Keywords: Jews -- Politics and government; Jewish leadership -- History; Leadership -- Religious aspects -- Judaism; Authority -- Religious aspects -- Judaism; Electronic books